Grip strength as a surrogate measure of strength, functional, and metabolic parameter increases in breast cancer survivors undergoing an exercise regimen - Colin E. Champ; Chris Peluso; Christie Hilton; Jared Rosenberg; Rhyeli Krause; Alexander K. Diaz; David J. Carpenter (Scientific Reports)
Abstract Grip strength, a surrogate for quantifying strength, correlates with function and longevity. However, this relationship is less clear in women with breast cancer. 138 women undergoing oncologic treatment for breast cancer were enrolled across three institutional review board-approved protocols with three months of resistance training with pre and post assessment of body composition, phase angle, functional movement screen (FMS), balance, weight lifted (load), quality of life, activity levels, and hand grip strength. Significant increases in maximum, minimum, and mean grip strength were seen. Mean grip strength increased by 12.6% and 3.5 kg. Right/left (R/L) mismatch significantly decreased from baseline to post-intervention (13.3 to 8.7%). On univariable analysis, greater baseline mean grip strength was associated with younger age, greater baseline FMS, composite load lifted, activity levels, and decreased R/L balance mismatch. On multivariable analysis, greater mean grip strength was independently associated with greater baseline mobility and composite load lifted. Baseline mean grip strength was associated with baseline lower bodyfat percentage and greater muscle mass, whole body phase angle, and resting metabolic rate (all significant on multivariable analysis, R2 = 0.247). Grip strength may be a valuable surrogate biomarker within breast cancer survivorship care, particularly in resource-limited settings.